A Bibliometric Approach to the Publications in the Field of International Business in the Scopus Database (2020)
This article carries out a bibliometric characterization of research in the field of international business, manifested in the academic literature that is indexed in the Scopus database, as is the case of scientific articles and other means of publication. On a methodological level, a descriptive study is carried out based on the measurement system of Scimago Journal & Country Rank (SJR). Therefore, the results show the historical behavior of the media categorized by continents; the countries with the largest amount of literature; the total number of journals per quartile; and additionally identify some indicators that can influence research production in the field of study. It is concluded that the developed countries with significant budgets for research such as the United Kingdom, the United States, the Netherlands, Germany, among others, are currently the countries with the highest output of scientific publications indexed in Scopus. Keywords: Scientific Publications, International Business, Field, Bibliometric.